Climate Risk Management for Agricultural Extension: Processes, Experiences, And Lessons Learnt from Ethiopia - Belay, Berhanu; Amha, Yosef; Ambaw, Gebermedihin; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change poses significant pressure and risks in agriculture, particularly for smallholder farmers who contribute significantly to Ethiopia's food systems. Integrating climate risk management (CRM) into agriculture extension services is critical for building the resilience, sustainability, and adaptive capacity of agricultural systems and rural communities in the face of climate change. Furthermore, capacity-building initiatives on climate knowledge innovations in climate-smart agriculture (CSA), CRM, and climate information services (CIS) are crucial for strengthening the resilience of agricultural value chains and food systems to climate shocks and market disruptions. In this regard, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) and its partner, the International Research Institute for Climate and Society (IRI), developed a customized manual on climate risk management in Agriculture for extension (CRMAE) to bridge the knowledge gap on climate risk management in agriculture. AICCRA partners with the GIZ Climate Sensitive Innovations for Land Management (CLM) projects and public universities to reach out to thousands of farmers using a Training of Trainers (ToT) approach. The training process comprises four stages: AICCRA-IRI trains university staff, who then train Subject Matter Specialists (SMS), Development Agents (DAs), and facilitators. In turn, these SMS and DAs train community leaders and model farmers, who finally pass on the knowledge to farmers at the grassroots level. Training of trainers (ToT) are supported by solid backing and supervision at each stage to ensure the approach's effectiveness and adequately reach out to all farmers exposed to climate change. The ToT had a robust monitoring and evaluation modality. The training was implemented through a co-financing approach, where AICCRA funded the expenses for trainers (university staff, ToTs), while GIZ-CLM covered costs for trainees per diem, logistics (travel to and from universities), refreshments, stationery, and other expenses. The universities contributed in-kind support, including staff time, dormitory accommodations for trainees, training rooms, and transportation for field visits. This exemplary collaboration resulted in the training of over 36 senior university staff (Grossi et al. 2022) and 257 junior and postgraduate staff (Belay et al. 2023). The SMS/DA/facilitators training included an action plan to train farmers and community leaders and integrate CRMAE into annual and five-year grassroots plans. Capacity building training provided by AICCRA Ethiopia activity leaders, with the support of partners including GIZ and national universities. Through this partnership, a total of 814 SMSs, DAs and field facilitators have been trained (Table 1). In the current year, 2024, smallholder farmers at the grassroots level will be trained. Overall, the established collaboration facilitates the development of diverse learning materials, innovative teaching methods, and interdisciplinary curricula that can effectively engage trainees of all ages and backgrounds. Additionally, co-resourcing fosters partnerships and networking opportunities, creating a supportive ecosystem, enhancing the effectiveness of CRMAE initiatives, and empowering farmers and communities to address climate challenges more effectively.